2020
DOI: 10.1155/2020/7656232
|View full text |Cite
|
Sign up to set email alerts
|

CVT in the Peripartum Period: A Diagnostic Dilemma

Abstract: Women in the peripartum period can develop headache with a variety of etiologies that require a multidisciplinary approach if unresponsive to treatment (Stella et al. 2007). Neuroimaging needs to be undertaken even occasionally in the absence of focal neurologic signs to rule out life-threatening causes of headache. We present the case of a 23-year-old woman who presented postpartum with severe frontal headache without other neurologic symptoms. Treatment was initiated for tension type, then subsequently postd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Pregnancy and postpartum period are associated with complex physiological changes and adaptation mechanisms, which can lead to altered homeostasis and a high risk of complications [ 1 ]. The main causes for increased CVT risk during the postpartum period are the hypercoagulability related to pregnancy, cesarean delivery, infections, blood loss during delivery and dehydration, fluctuations of intracranial pressure during labor, hypertensive complications of pregnancy, and even loss of cerebrospinal fluid after dural puncture [ 12 , 13 ]. The prothrombotic state during pregnancy results from a shift in the equilibrium between the fibrinolytic and hemostatic system to prevent severe hemorrhage during labor.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy and postpartum period are associated with complex physiological changes and adaptation mechanisms, which can lead to altered homeostasis and a high risk of complications [ 1 ]. The main causes for increased CVT risk during the postpartum period are the hypercoagulability related to pregnancy, cesarean delivery, infections, blood loss during delivery and dehydration, fluctuations of intracranial pressure during labor, hypertensive complications of pregnancy, and even loss of cerebrospinal fluid after dural puncture [ 12 , 13 ]. The prothrombotic state during pregnancy results from a shift in the equilibrium between the fibrinolytic and hemostatic system to prevent severe hemorrhage during labor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CVT represents 2 to 57% of pregnancy-related strokes [15], and the majority of cases appear in the postpartum period [16] with the main causes of increased risk during the postpartum period. pregnancy-related hypercoagulability, cesarean delivery, infections, blood loss during delivery and dehydration, fluctuations in intracranial pressure during labor, hypertensive complications of pregnancy, and even loss of cerebrospinal fluid after dural puncture [17]. Acute treatment of stroke is associated with the risk of bleeding, and current recommendations for the treatment of acute stroke do not apply to women in the puerperium; therefore, recommendations for acute treatment with intravenous thrombolysis (IVT) and/or mechanical thrombectomy (MT) are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that enhance thrombotic risk are added to the above modifications, such as cesarean delivery, anemia secondary to blood loss, dehydration, intracranial pressure fluctuations during labor, pre-eclampsia and eclampsia, and the dural puncture during spinal analgesia [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The loss of cerebrospinal fluid after dural puncture may lead to decreased intracranial pressure, compensatory venous and arterial dilation, decreased venous flow, endothelial damage, and activation of the coagulation system [ 26 ]. Silvis et al demonstrated that women after delivery present an increased risk of CVT, but not during pregnancy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%